(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
In the present paper an attempt has been made to assess the value and attitude of the female graduates of different religions towards various issues i.e. Religious Value, Social Value, Democratic Value, Aesthetic Value, Economic Value, Knowledge Value, Hedonistic Value, Family Prestige Value, Health Value etc. every thing is changing very rapidly, be it our culture, customs, norms and values. Changes have been seen in every phase of life has emerged as a result of modernization.